Caffeine restricts hepatitis B virus transcription by inhibiting γ-H2AX formation - Liao, Fangli; Sun, Siyi; Huang, Wenjuan; Yang, Liping; Hu, Qin; Chen, Weixian; Tu, Chaolin; Jiang, Linshan (Frontiers in Microbiology, 2025)
The influence of caffeine on human health has been widely studied, but its relevance to hepatitis B virus (HBV) remains unclear. Here, we report that exogenous caffeine suppresses HBV RNA and core protein expression in hepatoma cells. Mechanistically, caffeine reduces the DNA damage marker γ-H2AX, which in turn diminishes HBV transcription. Functional assays revealed that γ-H2AX enhances HBV core promoter activity by facilitating the recruitment of peroxisome proliferator–activated receptor-α (PPARα). Chromatin immunoprecipitation confirmed that reduced γ-H2AX levels impair the binding of PPARα to the HBV core promoter. These findings establish a γ-H2AX–PPARα signaling axis that promotes HBV transcription and demonstrate that caffeine interferes with this pathway. In summary, our study demonstrated that γ-H2AX may serve as a nutritionally targetable node, supporting dietary and adjunct strategies for HBV management.